2017
DOI: 10.1002/jum.14461
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean Delivery Changes the Natural Position of the Uterus on Transvaginal Ultrasonography

Abstract: Cesarean delivery can change the uterine flexion angle to a more retroflexed position. Therefore, all women with a history of cesarean delivery should undergo a transvaginal US examination before any gynecologic surgery or intrauterine device placement to reduce the possibility of surgical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The uterus is anteflexed in about 50% of women in a normal population [ 19 ], but tends to change position into more pronounced anteflexion post-cesarean. While some authors conclude that a CS changes the uterus into a retroflexed position [ 20 ], most sonographic studies of post-cesarean uteri show an overall increase of anteflexion up to a prevalence of 80% [ 21 ]. This cohort shows similar findings with predominantly anteflexed uteri post-cesarean which could indicate that CS increases uterine anteflexion.…”
Section: Discussionmentioning
confidence: 99%
“…The uterus is anteflexed in about 50% of women in a normal population [ 19 ], but tends to change position into more pronounced anteflexion post-cesarean. While some authors conclude that a CS changes the uterus into a retroflexed position [ 20 ], most sonographic studies of post-cesarean uteri show an overall increase of anteflexion up to a prevalence of 80% [ 21 ]. This cohort shows similar findings with predominantly anteflexed uteri post-cesarean which could indicate that CS increases uterine anteflexion.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, non‐gravid patients demonstrate a significantly greater incidence of uterine retroflexion in women with a history of Cesarean delivery, as reported by three separate groups 11–13 . In a retrospective review of 641 transvaginal ultrasound images, Sanders and Parsons reported uterine retroflexion in 27% of patients who had undergone Cesarean delivery, as opposed to 1% in multiparous patients without a history of Cesarean delivery and none in nulliparous patients 11 .…”
Section: Discussionmentioning
confidence: 88%
“…During pregnancy, the uterus of the mother will undergo a series of changes as the fetus develops, including the increase in uterine volume and weight, the increase in blood flow in various parts of the uterus, and changes in nerve distribution, tissue hormone level, and their receptors. When the fetus is full term, the uterus will undergo a series of changes as delivery occurs to ensure that all changes that occurred during pregnancy will recover or be restored to pre-pregnancy status to fully prepare for the next pregnancy (Kaelin Agten et al, 2018). The uterus and ovaries are dependent on and interact with each other in morphology and regulation of endocrine secretion during recovery of reproductive function in female animals.…”
Section: Discussionmentioning
confidence: 99%
“…At the uterus, the internal iliac artery supplies the uterus and is anastomosed with the ovarian arteries (branch of the aorta) and is connected to the inferior and superior vaginal blood vessels. At the same time, the lymph nodes of the uterine body are 168 H. Yang et al: Comparative analysis of differentially expressed miRNAs in ovary and uterus extended to the pelvic cavity on one side and the para-aortic lymph nodes on the other side (Ercoli et al, 2010;Lanciego et al, 2012;Abe et al, 2014;Hamadeh et al, 2018). At the endocrine secretion level, the ovaries synthesize and secrete steroid hormones such as E 2 and P 4 .…”
Section: Introductionmentioning
confidence: 99%